Structure-properties relationship study in niobium oxide containing GaO3/2-LaO3/2-KO1/2 gallate glasses. (April 2019) - Skopak, T.; Serment, B.; Ledemi, Y.; Dussauze, M.; Cardinal, T.; Fargin, E.; Messaddeq, Y.
Graphical abstract: Photographs and Raman spectra of the (100-x)(69GaO3/2 -11LaO3/2 -20KO1/2 )-xKNbO3 gallate compositions with x = 0 ; 5 ; 10 ; 14 ; 17 and 20 mol.% (a, b, c, d, e and f, respectively). Highlights: Gallate glasses were prepared using glass melting technique. The glass network is mainly composed of gallium and niobium ions respectively in tetrahedral [GaO4 ] − and octahedral [NbO6 ] sites. The niobium ions, in octahedral sites, form corner shared [NbO6 ] glass subnetworks. Abstract: The investigation has been devoted to the effect of the KNbO3 in a gallate based glasses of composition (100-x) (69GaO3/2 -11LaO3/2 -20KO1/2 ) – x KNbO3 with x varying from 0 to 20 mol.% allowing the use of standard melt technique. The thermal and optical properties were characterized and the local structure has been investigated by Raman spectroscopy. The gallium ions are mostly found in tetrahedra thanks to charge balancing of potassium and lanthanum ions. The continuous increase of the KNbO3 concentration gives rise to the progressive formation of a niobate subnetwork composed of corner shared NbO6 octahedra which does not depolymerize the gallate glass network. This addition has a limited impact on the multiphonon edge in the infrared while it causes a significant increase of the refractive index. For KNbO3 concentrations above 14 mol.% a phase separation occurs due to the absence of formation of a mixed gallo-niobate glass skeleton.